Stages of formation of the investment strategy of the enterprise - Полозова, Т. В.; Кравченко, М. В. (ХНУРЕ, 2021)
The main tasks of formation the investment strategy of the enterprise can include: setting strategic goals of investment activities, determination of priority areas and appropriate forms on the basis of strategic investment analysis; selection, evaluation and ranking of acceptable investment projects; optimization of the structure of investment resources and their distribution; monitoring and adjustment depending on changes of influencing factors.
DOI: 10.30837/978-966-659-334-7
Keywords: investment strategy; investment activities of the enterprise